Future Directions in Facial Rejuvenation - Sherber, Noëlle S.; Rad, Ariel N. (Facial Plastic Surgery, 2014)
Future directions in the advancement and refinement of facial rejuvenation techniques represent a response to patient demand for higher aesthetic impact with less procedural downtime and with minimal scarring as evidence of previous surgery. With surgical procedures, the trend of innovation in response to demand has been toward more minimally invasive approaches that have the predictability and durability of results of more traditional approaches. With nonsurgical procedures, there have been new developments in achieving more significant aesthetic improvements with less downtime and less invasively.
Keywords: facelift; minimally invasive; facial rejuvenation; scar treatment; revolumizing